2010
DOI: 10.1128/jvi.00892-10
|View full text |Cite
|
Sign up to set email alerts
|

Functional Divergence among CD103+Dendritic Cell Subpopulations following Pulmonary Poxvirus Infection

Abstract: A large number of dendritic cell (DC) subsets have now been identified based on the expression of a distinct array of surface markers as well as differences in functional capabilities. More recently, the concept of unique subsets has been extended to the lung, although the functional capabilities of these subsets are only beginning to be explored. Of particular interest are respiratory DCs that express CD103. These cells line the airway and act as sentinels for pathogens that enter the lung, migrating to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 41 publications
3
37
1
Order By: Relevance
“…In contrast, recipients of CX3CR1 +/+ NK cells showed no protective response. As professional APCs, DCs are the key instigators of the adaptive immune response (16,17). Our evidence presented in this study shows that expression of CX3CR1 is crucial for DC-mediated protection from a VV lung infection.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In contrast, recipients of CX3CR1 +/+ NK cells showed no protective response. As professional APCs, DCs are the key instigators of the adaptive immune response (16,17). Our evidence presented in this study shows that expression of CX3CR1 is crucial for DC-mediated protection from a VV lung infection.…”
Section: Discussionmentioning
confidence: 68%
“…In our model, we observed a reduced VV-specific T cell response in infected CX3CR1 2/2 mice compared with control mice, suggesting that this was at least partly how the DCs exerted their protective influence. In fact, very recently, the lung-migrating CD103 + DC population was implicated as the major contributor to CD8 T cell activation following poxvirus infection (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 These results and comparable findings in other models of viral infection suggested that among the DC subsets present in the MLNs, the migrant langerin + CD103 + CD11b − respiratory DCs are the most potent APCs for the activation of naive antiviral T cells after viral lung infection. 65,66 After stimulation by DCs, the now activated naive T cells undergo multiple rounds of cell division in the MLNs and primarily differentiate into antiviral effector T cells. These freshly activated effector T cells emigrate out of the MLNs to the site of infection (ie, the infected lungs), where they can further interact with recently recruited viral antigen-displaying inflammatory DCs.…”
Section: Cellular Immunitymentioning
confidence: 99%
“…Surface phenotype of lung CD11c+ cells was analysed for CD11b and CD103 expression as previously described [18][19][20]. After counting, lung CD11c+ cells magnetically purified as described above were stained with FITC-conjugated anti-CD103 (clone M290; BD Biosciences) and phycoerythrin (PE)-conjugated anti-CD11b antibody (clone M1/70; BD Biosciences) [21].…”
Section: Flow Cytometrymentioning
confidence: 99%